2017
DOI: 10.2196/jmir.7082
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward the Ethics of Research Using Social Media: A Systematic Review

Abstract: BackgroundAlthough primarily used for social networking and often used for social support and dissemination, data on social media platforms are increasingly being used to facilitate research. However, the ethical challenges in conducting social media research remain of great concern. Although much debated in the literature, it is the views of the public that are most pertinent to inform future practice.ObjectiveThe aim of our study was to ascertain attitudes on the ethical considerations of using social media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(143 citation statements)
references
References 72 publications
2
124
0
2
Order By: Relevance
“…Despite ethical considerations, which were considered at every level within this research, [90], the authors are in agreement with Golder, Amed, Norman and Booth's recently stated viewpoint that 'we cannot afford to miss the considerable potential of social media research and its unique contribution to knowledge' [91]. The aim of the current research is to gain an understanding of how people use open Facebook groups for their emotional and mental health needs, and to gain an insight into how they support each other through these groups.…”
Section: Social Networking Sites and Mental Health Supportsupporting
confidence: 54%
“…Despite ethical considerations, which were considered at every level within this research, [90], the authors are in agreement with Golder, Amed, Norman and Booth's recently stated viewpoint that 'we cannot afford to miss the considerable potential of social media research and its unique contribution to knowledge' [91]. The aim of the current research is to gain an understanding of how people use open Facebook groups for their emotional and mental health needs, and to gain an insight into how they support each other through these groups.…”
Section: Social Networking Sites and Mental Health Supportsupporting
confidence: 54%
“…The majority of articles focused on ethical concerns at the intersection of social media and biomedical informatics published during the review period focus on the ethical conduct of research on and through these platforms [27][28][29][30][31][32][33], including consideration for particularly sensitive cases in mental health [34,35]. A few articles discuss the ethical issues associated with direct use of social media for health by patients and providers as they relate to HCI [36,37].…”
Section: Social Media and Online Communitiesmentioning
confidence: 99%
“…Their analysis revealed that Twitter users are generally aware that Twitter data is public by default and were not opposed to the use of publicly available data for health monitoring activities provided that the data are anonymized and aggregated to remove personally identifiable information. Golder et al [16] examined the attitudes of both social media users and researchers on using social media as a data source for research and had similar responses. Importantly, previous studies have also shown that users unwittingly share private information on Twitter, suggesting they may not be aware of what can be inferred from their publicly available data.…”
Section: In Privacy and Ethicsmentioning
confidence: 99%